FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN FINTECH SEBAGAI ALAT PEMBAYARAN DIGITAL - Putu Emy Trimisyantari Putri; Hascaryani, Tyas Danarti (Contemporary Studies in Economic, Finance and Banking, 2022)
The growth of the fintech ecosystem in Indonesia has been rapidly increasing in the past five years, until Q2 2020 362 fintech companies are members of the Indonesian Fintech Association (AFTECH). The increase in the adoption of fintech by the public can also be seen from the increase in the value of digital payment transactions by 122,89% from 2017 to 2021. The community began to turn into a cashless society during the Covid-19 pandemic. This research aims to determine the effect of variables from the Technology Acceptance Model (TAM) and consumer knowledge on the interest in transacting using e-wallets. This study uses a quantitative approach with multiple linear regression method. Data were obtained through questionnaires distributed to 96 respondents from generation X and 96 respondents from generation Z who had transacted using e-wallets and lived in Denpasar City. Statistical tests were carried out using the help of SPSS software version 26. The results showed that the variable perceived usefulness, perceived ease of use, and consumer knowledge partially and simultaneously proved to have a positive and significant influence on the intention to transact using e-wallets as a digital payment in both generation X and generation Z.